2012
DOI: 10.1099/vir.0.041731-0
|View full text |Cite
|
Sign up to set email alerts
|

A third gyrovirus species in human faeces

Abstract: Until 2011 the genus Gyrovirus in the family Circoviridae consisted of a single virus (Chicken anemia virus or CAV) causing a common immunosuppressive disease in chickens when a second gyrovirus (HGyV) was reported on the skin of 4 % of healthy humans. HGyV is very closely related to a recently described chicken gyrovirus, AGV2, suggesting that they belong to the same viral species. During a viral metagenomic analysis of 100 human faeces from children with diarrhoea in Chile we identified multiple known human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
73
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 32 publications
0
73
1
Order By: Relevance
“…However, other potential members of the genus Gyrovirus have been recently discovered in humans and birds. These novel gyroviruses (GyVs) have been identified in human skin (human gyrovirus (HGyV) [74]) and feces (GyV3 through GyV6; [8,61,62]), chicken serum (avian gyrovirus 2 (AGV2) [66]) and meat (GyV4 and GyV7; [8]) as well as spleen and uropygial gland tissues from sea birds (GyV8; [39]). Since HGyV and AGV2 may represent the same species [61], the genus Gyrovirus should soon be updated to reflect at least eight viral species.…”
Section: Reassignment Of the Genus Gyrovirus To The Family Anelloviridaementioning
confidence: 99%
“…However, other potential members of the genus Gyrovirus have been recently discovered in humans and birds. These novel gyroviruses (GyVs) have been identified in human skin (human gyrovirus (HGyV) [74]) and feces (GyV3 through GyV6; [8,61,62]), chicken serum (avian gyrovirus 2 (AGV2) [66]) and meat (GyV4 and GyV7; [8]) as well as spleen and uropygial gland tissues from sea birds (GyV8; [39]). Since HGyV and AGV2 may represent the same species [61], the genus Gyrovirus should soon be updated to reflect at least eight viral species.…”
Section: Reassignment Of the Genus Gyrovirus To The Family Anelloviridaementioning
confidence: 99%
“…etagenomic analyses of human fecal samples have shown frequent coinfections with known enteric pathogens (26,70) and the presence of numerous novel viral species, particularly members of the Picornaviridae (20,31,33,37,40,51), Astroviridae (26,27,41) Parvoviridae (39,45), and Circoviridae (49,58) families of small enteric viruses. Metagenomics studies of animal feces have similarly shown frequent coinfections and yielded highly divergent viral species (10,16,25,30,43,44,50,52,53,57,60,61,64).…”
mentioning
confidence: 99%
“…Most recently, novel members of the Gyrovirus genus have been discovered in diseased chicken (Rijsewijk et al, 2011), but also in human faeces (Phan et al, 2012) and in healthy blood donors as well (Biagini et al, 2013a). The positive fish samples examined in our survey originated from 142 TARJÁN et al Hungarica 62, 2014 apparently healthy individuals.…”
Section: Discussionmentioning
confidence: 99%